The first step is to rearrange the inequalities. The first inequality would be
The second inequality would be
![y\text{ }<\text{ 2x - 9}](https://img.qammunity.org/2023/formulas/mathematics/college/2awr38xwq2sqv8ltj1xco0bbbyb8sgsel2.png)
![-\text{ 2y }\ge\text{ - 2x + 6}](https://img.qammunity.org/2023/formulas/mathematics/college/rfhhgu5fjh0aff5ewn776fgyivqhx8a5il.png)
We would divide both sides by - 2. This would cause the inequality symbol to reverse. It becomes
![y\text{ }\leq\text{ x - 3}](https://img.qammunity.org/2023/formulas/mathematics/college/qu8s6pmmt4qg4nsy2lkjbzxxw6n73989ll.png)
The next step is to plot both inequalites like normal linear equations
For the first inequality,
y = 9 - 2x
Let us input values for x to get corresponding y values
when x = -2, y = 13
When x = - 1, y = 12
When x = 0, y = 9
When x = 1, y = 7
When x = 2, y = 5
For the second inequality,
y = x - 3
Let us input values for x to get corresponding y values
when x = -2, y = - 5
When x = - 1, y = - 4
When x = 0, y = - 3
When x = 1, y = - 2
When x = 2, y = - 1
We would plot these points on a graph and we would get 2 straight lines.
The graph is shown in the attached photo.
The solution region is the darker region